The neurolinguistic approach (NLA) for learning and teaching foreign languages theory and practice - Germain, Claude (Cambridge Scholars Publishing, 2018)
Since its inception in Canada in 1998 as a method for teaching French as a second language in a school setting, the Neurolinguistic Approach to second-language acquisition (NLA) has expanded to several countries and is now also applied to teaching adults. Based on research in the neurosciences, psychology, and sociology, the NLA focuses on providing learners with the conditions necessary to acquire spontaneous communication skills in a classroom setting. By ensuring the independent development of effective communication and implicit competence in the second language, the NLA allows learners to.